Written Preparation for History Class - Marsenić, Miloš (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
Teaching is an organized and planned work process that accomplishes the tasks of upbringing and education. The success of teaching  depends  on  the  quality  of  planning.  The  lecturer  has  the obligation to perform planning continuously. Planning can be annual, monthly, and daily, and for the processing of each teaching unit, it is necessary to have the class prepared. Class is the basic time unit for planning  educational  work  in  the  school.  Each  lesson  must  be preceded by the appropriate written preparation of the teacher. It should not be an obligation but a need for the material to be successfully  mastered.  Every  class  is  special  and  with  good  preparation mistakes and shortcomings are minimized. Each writing preparation for a class has several phases: professional, didactic-methodical, and technical  preparation. After  these  phases,  the  making  of  written preparation is approached. It should contain the following elements: name of the school, name of the teacher, name of the subject, grade and class, date, the ordinal number of class, teaching topic, teaching unit, type of class, goals and tasks of the class, form of work, teaching methods, teaching aids, correlation with other subjects, class flow, homework,  the  layout  of  the  board  and  observations  about  the class. The methodology of teaching history has similarities with the methods of other subjects, but also its peculiarities, due to its subject of work, history.
Keywords: teaching; teaching planning; class; written preparation for class; history teaching methodology; elements of preparation for the class